2011
DOI: 10.1107/s1600536810052141
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Bis[2-(2-oxo-1,3-oxazolidin-3-yl)ethyl]-1H-benzimidazol-2(3H)-one

Abstract: The mol­ecular structure of the title compound, C17H20N4O5, contains a central fused-ring system, comprised of six- and five-membered rings. This unit is linked by C2 chains to two 2-oxo-1,3-oxazolidine five-membered rings. The central fused-ring system is essentially planar, with a maximum deviation of 0.008 (1) Å from the mean plane. Both oxazolidine five-membered rings are also nearly planar, with maximum deviations of 0.090 (1) and 0.141 (1) Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For asymmetric reactions of oxazolidin-2-ones, see: Evans et al (1993); Matsunaga et al (2005). For oxazolidin-2-one derivatives, see: Ouzidan et al (2011); Dardouri et al (2011)…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For asymmetric reactions of oxazolidin-2-ones, see: Evans et al (1993); Matsunaga et al (2005). For oxazolidin-2-one derivatives, see: Ouzidan et al (2011); Dardouri et al (2011)…”
Section: Related Literaturementioning
confidence: 99%
“…Some oxazolidin-2-ones have been used as chiral auxiliaries in a wide range of asymmetric reactions (Evans et al, 1993;Matsunaga et al, 2005). In a previous study, we reacted 1H-benzo[d]imidazol-2(3H)-one with bis(2-chloroethyl)amine hydrochloride in the presence of a catalytic quantity of tetra-n-butylammonium bromide to form 1,3-bis(2-(2- (Ouzidan et al, 2011). The study is extended to the synthesis of the 5-chloro analog to furnish the title compound (Scheme 1).…”
Section: S1 Commentmentioning
confidence: 99%
“…As a continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives Ouzidan, Kandri Rodi, Fronczek et al, 2011;Belaziz et al 2012), we reported in this paper the synthesis of benzimidazol-2-one derivative by action of propargyl bromide with 1Hbenzo[d]imidazol-2(3H)-one in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to furnish two compounds: di-substituted (Ouzidan, Kandri Rodi, Jasinski et al, 2011) and mono-substituted (Scheme 1).…”
Section: Sup-1mentioning
confidence: 99%
“…As a continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives (Ouzidan et al, 2011a(Ouzidan et al, , 2011b, we report in this paper the synthesis of a new benzimidazol-2-one derivative by action of benzyl chloride with 1H-benzimidazol-2-one in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to furnish the title compound (Scheme 1).…”
Section: Data Collectionmentioning
confidence: 99%